The Influence of Digital Literacy on Citizen Engagement and Participation in E-Government Services for Inclusive Digital Governance - Anzar, Muh.; Hasbullah, Hasbi; Asraf, Isman (Journal Social Civilecial, 2024)
This research aims to focus on the contribution of digital literacy in raising preferable citizen participation in e-government services, where most of the previous studies give prominence to technological factors and physical connectivity. The study endeavours to understand the impact of the extent to which these citizens understand and are capable of using the technologies on their ability to engage with e- government services. The study utilizes both survey data with interviews with citizens and public officials, which are used to supplement survey data. This research is said to establish that when the level of d-technology competencies of users improves, confidence, utilization, and the performance of e-government is boosted. In addition, the study finds that digital literacy moderates the effects of age, education, and socio-economic status on e-government use by reducing their effects. These findings stress the necessity of the digital literacy inclusion into public policy to provide equal opportunities for accessing digital authorities’ services. In this regard, the study assuming this important research gap offers a more robust framework that can enable the policymakers and the public administrators to develop more efficient and user-friendly e-government systems. The study concludes with specific recommendations on how to increase digital literacy by targeting appropriate educational interventions and involving relevant stakeholder within the digital inclusion frameworks cross-cultural communities.